Encountering Communism in a Cosmopolitan City: The Ducroux Case in the Eyes of the Singapore Press - Kankan Xie (BERITA: The Official Publication of the Malaysia/Singapore/Brunei Studies Group, Association for Asian Studies (AAS), 2019)
Scholars commonly regard the Comintern as having played a critical role in the emergence of the communist movement in late-colonial Malaya. When discussing the Comintern’s early influence, existing scholarships often use the arrest of Joseph Ducroux — alias Serge Lefranc, a French agent of the Comintern — in Singapore in June 1931 to illustrate the Comintern-China-Malaya connection. Additionally, historians have attached special meanings to the Ducroux Case, primarily because of the more significant repercussions it caused internationally. Laurent Metzger has conducted detailed research on Ducroux’s arrest in and eventual exile from Singapore between 1931 and 1932. While such an account is useful in demonstrating the incident’s international significance, little is known as to what immediate impression it created in the cosmopolitan port city. Moreover, it is also unclear how Singapore’s general public perceived communism when communist organizations had yet firmly established themselves in the British colony. This article seeks to make sense of such issues by investigating how the Singapore press reported on the Ducroux Case.